Pengaruh Profitabilitas, Kinerja Keuangan, Ukuran Perusahaan dan Solvabilitas terhadap Pertumbuhan Laba - Rahel Lumbantoruan; Sri Murni Agustin; Susanti Susanti; Ike Rukmana Sari (Mahesa Research Center, 2021)
To see and test whether the effect of profitability, financial performance, company size and solvency on profit growth (empirical study of the trade, service and investment sector) listed on the IDX for the period 2017-2019 is the purpose of this study. The data analysis method used is statistical analysis method and quantitative descriptive approach. This research is an explanation level research. A total of 177 companies are the total population obtained from companies listed on the IDX from 2017-2019. Samples were taken using purposive sampling technique. This technique is often used by other researchers because the samples obtained are early for the purpose of the study. Samples can be obtained from 14 companies. Data analysis used several analyzes, namely classical assumption test and multiple linear regression. This study shows that partially the profitability variable that has an effect on profit growth, while the financial performance, company size, and solvency variables do not have a significant effect on service companies listed on the Indonesia Stock Exchange. Simultaneously profitability, financial performance, company size and solvency also have no effect on profit growth in trade, services and investment sector service companies listed on the Indonesia Stock Exchange.